Keunggulan Dinar dan Dirham Sebagai Mata Uang Menurut al-Ghazali dan Ibnu Taimiyah - Subaidi Subaidi (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2018)
The presence of currency is very easy for people to meet daily needs compared to barter system. Before recognizing paper money as it is now, people used to use the currency of gold and silver, known as dinar and dirham. Many Muslim scholars have contributed greatly to his thinking about the concept of dinars and dirhams as currencies in Islam. Among them, are al-Ghazali and Ibn Taimiyah. Al-Ghazali realized the important role of dinar and dirham as currency. The role of dinars and dirhams of pure gold and silver as currency is very urgent and cannot be replaced by other goods, because dinars and dirhams have privileges, namely: scarcity, durable and favored.